The prognostic impact of daytime and seasonality of radiotherapy on head and neck cancer. (May 2021) - Elicin, Olgun; Koller Brolese, Eliane; Bojaxhiu, Beat; Sermaxhaj, Burim; Schanne, Daniel Hendrik; Mathier, Etienne; Lippmann, Jana; Shelan, Mohamed; Eller, Yannick; Aebersold, Daniel Matthias; Giger, Roland; Cihoric, Nikola
Highlights: Circadian rhythm was previously shown to correlate with treatment toxicity. This is the first study investigating the impact of seasons on oncologic outcome. Radiotherapy delivery in the darker half of the year yields better tumor control. Abstract: Background: The potential impact of daytime and season of radiotherapy application on prognosis is unclear. This was analyzed in a retrospective cohort of patients who were diagnosed with non-metastatic head and neck squamous cell carcinoma (HNSCC) and treated with definitive radiotherapy with or without chemotherapy. Materials and methods: Patient and tumor characteristics, treatment parameters and outcome until last follow-up or death were obtained. Median radiotherapy delivery daytime of each patient was categorized as morning (AM) and afternoon (PM). Treatment season was defined by median date of treatment course. Each year was divided into DARK and LIGHT according to equinoxes. Time-to-event endpoints were defined by first biopsy confirming the HNSCC. Results: Six hundred fifty-five cases were identified who were treated with (chemo)radiotherapy between 2002 and 2015. Median follow-up was 47 months. No significant heterogeneity in patient, tumor and treatment characteristics were observed between DARK and LIGHT or regarding median daily fraction time (X2 p  > 0.05). Five-year loco-regional control (73% vs. 61%; p  = 0.0108) and progression-free survival (51% vs. 43%; p  = 0.0374) were superior when radiotherapy was administered in DARK. Neither the daytime nor any other treatment time-related parameter affected prognosis. Conclusion: This is the first study investigating and presenting the prognostic impact of seasonality regarding the treatment course on loco-regional control and progression-free survival (DARK > LIGHT). The biological mechanism of action is unclear. These results should be interpreted with caution and our findings have to be validated externally.